Exploring the Vietnamese Consumer’s Trust in E-commerce - Nguyen, Thi Mai Anh (H. : ĐHQGHN, 2020)
Trust has been one of the main items of focus in e-commerce and many previous studies have provided useful contributions (e.g., Gefen 2000; McKnight, et al., 2000; 2002; Oliveira, et al., 2017, etc.). Prior research has found trust to play a significant role in shaping purchase intentions of a consumer (Oliveira, et al., 2017). In this paper, we explored the Vietnamese consumer trust in Internet shopping using three well identified dimensions of trust named personal; institutional and cognitive-based trust. A sample of 387 individuals from Hanoi was surveyed using a previously validated measurement instrument. Concerning the level of trust, it is revealed that online vendors which operate in Vietnamese market fail to appeal to their customers in regards to integrity, benevolence and assurance. Website quality is the only aspect that Vietnamese online shoppers think highly of. The findings of this research are of potential benefit to on-line vendors of all types who seek to engender consumer trust in their websites.